Clima organizacional y desempeño laboral de los trabajadores del área comercial de SEDALORETO, 2022 - Reguera del Castillo, Ingrid Karla (2023)
Our research objective is to establish the link between the organizational climate and the performance of employees in the commercial sector of Sedaloreto in 2022. To do this, we use a qualitative methodology. A type of correlation description method, Pearson correlation values are calculated from survey data by how variables are correlated by the predictable behavior of the sample or population. Considering the results, we can confidently say that the following hypothesis is correct. There is a significant correlation between the organizational climate and the performance of employees in the commercial district of Sedaloreto in 2022.